Effect of Hypervirulent Strains, Antibiotic Resistance, and Host Characteristics on Mortality of Klebsiella pneumoniae Bacteremia Patients at a Tertiary Referral Hospital in Denpasar, Indonesia - Adhy Candra, I Kadek Bayu; Suranadi, I Wayan; Darwinata, Agus Eka; Tarini, Ni Made Adi; Dharmika, Ida Ayu Gde Wahyudevi; Fatmawati, Ni Nengah Dwi (Faculty of Medicine, Universitas Padjadjaran, 2023)
Klebsiella pneumoniae bacteremia is one of the leading causes of sepsis that has a high mortality rate. The effect of multidrug resistance and different virulence of Klebsiella pneumoniae on mortality is still controversial. This study aimed to determine the impact of hypervirulent K. pneumoniae (hvKp), MDR, and clinical characteristics on mortality of K. pneumoniae bacteremia patients. A retrospective cross-sectional study was conducted on K. pneumoniae bacteremia cases of patients hospitalized at Professor dr. I.G.N.G Ngoerah General Hospital from December 1, 2020, to May 31, 2021. A positive PCR of rmpA, iucA genes, and/or a positive string test was identified as hvKp. The mortality rate of 51 K. pneumoniae bacteremia patients samples (aged 0-74 years) was 72.5%, in which 9.8% (5/51) of them were hvKp and 51% of the isolates (26/51) produced the Extended Spectrum Beta Lactamase (ESBL). Furthermore, 9.8% (5/51) of the cases were carbapenem-resistant. Thus, hvKp, MDR, gender characteristics, and comorbidities do not significantly affect the mortality of K. pneumoniae bacteremia patients. Multivariate logistic regression analysis showed that sepsis (odds ratio (OR) 4.29; p=0.038) and adult age group (mean 50 years) (OR 3.75; p=0.039) are independent predictors with a significant effect on mortality of K. pneumoniae bacteremia patients. Careful and integrated management of K. pneumoniae bacteremia patients is essential for better outcomes, especially in sepsis and elderly patients. Although hvKp prevalence is low, emerging MDR-hvKp in health facilities is a severe concern for further actions and research.